Penerapan Hukum Kepailitan Dalam Penyelesaian Utang-Piutang - Alya Afifa Riyadi; Aulia Az-zahra; Bilhaya athar; Gilang Annugrah; Mayluna Ardiaty; Helfira Citra (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
Debt issues are a common problem in the world of economics, both for individuals and companies. The inability of debtors to repay maturing debts can cause losses for creditors and legal disputes. To overcome this, bankruptcy law and Debt Payment Postponement (PKPU), as regulated in Law Number 37 of 2004, are available as mechanisms for collective and structured debt settlement. This paper aims to examine the application of bankruptcy law in debt settlement in Indonesia, explain the stages of the bankruptcy process, identify the parties involved and their roles, and analyze the legal implications for debtors and creditors. The research method employed is a normative juridical approach, involving a literature study that examines laws, regulations, and scientific journals found on the internet. The results of the study show that bankruptcy law provides legal certainty and protection through the fair distribution of bankruptcy assets based on the pari passu pro rata parte principle.